Growth Differentiation Factor 15 Predicts Cancer Death in Patients With Cardiovascular Risk Factors: The J-HOP Study - Negishi, Keita; Hoshide, Satoshi; Shimpo, Masahisa; Kario, Kazuomi (Frontiers in Cardiovascular Medicine, 2021)
Background: Disease-related anorexia-cachexia is associated with poor prognosis of patients with cardiovascular disease (CVD) or cancer. Growth differentiation factor-15 (GDF-15) has emerged as a central regulator of appetite and body weight. However, the exact role of GDF-15 in lean patients has not been elucidated. Aim: Our aim is to evaluate whether the association of GDF-15 with mortality, including cancer death, differs according to body mass index (BMI) level. Methods and Results: We collected blood samples from 4,061 patients with CV risk factors who were enrolled in the nationwide practice-based J-HOP (Japan Morning Surge-Home Blood Pressure) study. Serum GDF-15 levels were determined by immunoassay analysis. During a mean follow-up period of 6.6 years, we observed 174 (6.7/1000 person-year) all-cause deaths, 68 (2.6/1000 person-year) cancer deaths, and 56 (2.2/1000 person-year) CV deaths. Patients were stratified according to the cut-points of GDF-15 at 1,200 ng/L and BMI at 22.5 and 25.0 kg/m2. The association between the GDF-15/BMI based study groups and each outcome was evaluated by Cox-proportional hazard models with adjustment for established risk factors. The multivariate Cox regression model showed that patients with elevated GDF-15 (≥1,200 ng/L) and low BMI (<22.5 kg/m2) were significantly associated with increased risk of all outcomes [all-cause death, hazard ratio (HR) 3.15, 95% confidence interval (CI) 1.85–5.34, p < 0.001; cancer death, HR 3.52, 95%CI 1.64–7.57, p = 0.001; CV death, HR 2.88, 95%CI 1.20–6.92, p = 0.018, respectively] compared to a reference group with non-elevated GDF-15 and normal BMI (22.5–25.0 kg/m2). In analyses of a subgroup with low BMI (<22.5 kg/m2), patients with elevated GDF-15 had 4.79-fold increased risk of cancer death and 11-fold greater risk of CV death when compared with patients with non-elevated GDF-15 (<1,200 ng/L) after adjustment for established risk factors. Conclusion: In patients with CV risk factors, GDF-15 was associated with all-cause, cancer, and CV death. This relationship was especially remarkable in patients with low BMI. The serum GDF-15 levels in patients with low BMI might be a useful marker to identify the potential for anorexia-cachexia associated with CVD and cancer.